Exploring the emotional and behavioural reactions to receiving personalized melanoma genomic risk information: a qualitative study3. (4th March 2019) - Fenton, G.L.; Smit, A.K.; Keogh, L.; Cust, A.E.
Summary: Background: There is a need for greater understanding of the spectrum of emotional and behavioural reactions that individuals in the general population may experience in response to genomic testing for melanoma risk. Objectives: To explore how individuals in the general population respond to receiving personalized genomic risk of melanoma. Methods: Semistructured interviews were undertaken with 30 participants (aged 24–69 years, 50% female, 12 low risk, eight average risk, 10 high risk) recruited from a pilot trial in which they received personalized melanoma genomic risk information. We explored participants' emotional and behavioural responses to receiving their melanoma genomic risk information. The qualitative data were analysed thematically. Results: Many participants reported a positive response to receiving their melanoma genomic risk, including feelings of happiness, reassurance and gaining new knowledge to help manage their melanoma risk. Some participants reported short‐term negative emotional reactions that dissipated over time. Most individuals, particularly those who received average or high‐risk results, reported making positive behaviour changes to reduce their melanoma risk. Emotional and behavioural responses were linked to participants' expectations for their risk result, their pre‐existing perception of their own melanoma risk, their existing melanoma preventive behaviours and their genomic risk category. Conclusions: Personalized melanoma genomic risk information alongside education and lifestyle counselling is favourably received by people without a personal history and unselected for a family history of melanoma. Participants described increased knowledge and awareness around managing skin cancer risk and improved sun protection and skin examination behaviours. Any initial feelings of distress usually dissipated over time. Abstract : What's already known about this topic? Previous research suggests there is minimal emotional and behavioural impact of delivering personalized genomic risk information (based on common, low‐to‐moderate‐penetrance variants) to healthy individuals in the general population. Little is known about emotional and behavioural reactions of the general population to melanoma genomic risk information and whether this information could elicit positive sun protection and skin examination behaviours. What does this study add? This qualitative study found that participants' reported emotional and behavioural responses to receiving personal genomic risk results were linked to their expectations for their risk result, their pre‐existing perception of their own melanoma risk, their existing melanoma preventive behaviours and their genomic risk category (low, average, high). Many participants experienced positive emotional reactions to receiving personalized melanoma genomic risk information and reported making subsequent positive lifestyle behaviour changes. What are the clinical implications of the work? Personalized melanoma genomic risk information alongside education and lifestyle counselling is favourably received by the general public and might lead to improved sun protection and skin examination behaviours. Any initial feelings of distress will probably dissipate over time. These findings could guide the preparation of educational and support resources for clinicians, patients and the community to maximize the benefits and minimize the harms of genomic testing at a population level. Linked Editorial:  Nelson et al. Br J Dermatol 2019;180 :1271–1273 . Linked Comment:  McInerney‐Leo and Finnane. Br J Dermatol 2019;180 :1288–1289 . Plain language summary available online Respond to this article